(untitled) (American Journal of Islam and Society, 2010)
Jihad has become a normal English word, a term to describe irrational violence, “holy war,” terrorism, and the generally rather nasty things that “bad Muslims do.” John Kelsay, in this wonderfully succinct and accessible work, wants to argue that the real issue in discussing jihad is to make sense of legitimate violence and how it may be deployed, and hence to locate the discourse within an existing discussion about just war theory. I am not generally sympathetic to the use of the comparable frame of just war theory because, as a juridical and ethical concept it is rather limited, arising as it does out of a particular politico-theological context of medieval Catholicism. Having said that, any serious attempt to nuance jihad’s meaning in the contemporary world, to contextualize the discourse adequately and historically, and to pose difficult questions to those who appropriate it on the basis of a claim toward establishing justice and acting in a just cause is welcome. Kelsay is interested in the contemporary debate about the nature of political ethics among Muslims. His book is not just an attempt to “whitewash” Muslims and their theologies from any culpability in the acts and ideologies of the likes of al-Qaeda. While he does interrogate the theological and juridical reasoning of such terrorists, what he wants to show is not only their distance from historically grounded narratives of jihad, but also how their reasoning may be shared. It is indeed foolish to argue that jihadi ideology has nothing to do with reasoning about jihad as such; it is counterintuitive and unhelpful. He also wants to indicate how the language of just war is mutually supportive between the rhetoric of the “war on terror” and al-Qaeda’s war on the “Zionist-Crusaders” (which is, in theological terms, the subject of a forthcoming book by Alia Brahimi to be published by Cambridge University Press) ...